Human Health Risk Assessment from Consumption of Heavy Metal Contaminated Fish from Baraila Lake, Vaishali, Bihar, India - Renu Anand; Vijay Kumar (American Journal of Bioscience and Clinical Integrity, 2025)
Background: Baraila Lake, a vital aquatic ecosystem in Bihar, supports local fisheries but is vulnerable to anthropogenic heavy metal contamination, posing threats to aquatic life and human health. Objectives: This study investigated the bioaccumulation of heavy metals (Pb, Cd, Cr, Ni, Zn, Cu) in six fish species from different trophic levels and assessed the associated health risks for consumers. Methods: Fish samples (Labeo rohita, Catla catla, Cirrhinus mrigala, Channa striatus, Heteropneustes fossilis, Wallago attu) were collected seasonally. Muscle tissues were analyzed using Atomic Absorption Spectrophotometry (AAS). Health risk assessment was performed using Estimated Daily Intake (EDI), Target Hazard Quotient (THQ), Hazard Index (HI), and Carcinogenic Risk (CR) models following USEPA guidelines. Results: Metal concentrations followed the order: Zn > Cu > Cr > Pb > Ni > Cd. Carnivorous species, particularly W. attu, showed significantly higher (p<0.05) bioaccumulation than herbivorous species. Concentrations of Pb (0.56 mg/kg) and Cr (1.24 mg/kg) in W. attu exceeded FAO/WHO limits. Risk assessment indicated THQ >1 for Pb and Cr in children consuming W. attu. The HI values indicated significant cumulative non-carcinogenic risk (HI > 2.5 for W. attu), and the Carcinogenic Risk for Cr exceeded the acceptable limit of 10⁻⁴. Conclusion: Consumption of fish, especially carnivorous species, from Baraila Lake poses considerable health risks. The findings highlight the influence of trophic level on bioaccumulation and underscore the urgent need for monitoring, remediation, and public awareness.